Low dimensional representation of face space by face‐selective inferior temporal neurons. (4th May 2017) - Salehi, Sina; Dehaqani, Mohammad‐Reza A.; Esteky, Hossein
Abstract: The representation of visual objects in primate brain is distributed and multiple neurons are involved in encoding each object. One way to understand the neural basis of object representation is to estimate the number of neural dimensions that are needed for veridical representation of object categories. In this study, the characteristics of the match between physical‐shape and neural representational spaces in monkey inferior temporal (IT) cortex were evaluated. Specifically, we examined how the number of neural dimensions, stimulus behavioral saliency and stimulus category selectivity of neurons affected the correlation between shape and neural representational spaces in IT cortex. Single‐unit recordings from monkey IT cortex revealed that there was a significant match between face space and its neural representation at lower neural dimensions, whereas the optimal match for the non‐face objects was observed at higher neural dimensions. There was a statistically significant match between the face and neural spaces only in the face‐selective neurons, whereas a significant match was observed for non‐face objects in all neurons regardless of their category selectivity. Interestingly, the face neurons showed a higher match for the non‐face objects than for the faces at higher neural dimensions. The optimal representation of face space in the responses of the face neurons was a low dimensional map that emerged early (~150 ms post‐stimulus onset) and was followed by a high dimensional and relatively late (~300 ms) map for the non‐face stimuli. These results support a multiplexing function for the face neurons in the representation of very similar shape spaces, but with different dimensionality and timing scales. Abstract : There is a statistically significant match between the face physical similarity and the neuronal spaces only in the face selective neurons while a significant match was observed for non‐face objects in all neurons regardless of their category selectivity. Face selective neurons convey an early and low dimensional representation of face which is followed by a late and high dimensional representation of non‐face stimuli. Non‐face neurons showed late and high dimensional representation of non‐face stimuli. These results support a multiplexing function for the face neurons in representation of highly similar shape spaces but with different dimensionality and timing scales.